The role-emerging, inter-professional clinical placement: Exploring its value for students in speech pathology and counselling psychology - Ciccone, Natalie; Hersh, Deborah; Priddis, Lynn; Peterson, Amanda (Speech Pathology Australia, 2013)
This paper examines the experience of a speech pathology and a counselling psychology student in a role-emerging, interprofessional clinical placement. Qualitative descriptive analysis was used to explore student and staff perceptions of the placement which took place within a prerelease detention centre, housing up to six women and their young children, within the Department of Corrective Services. Student reflections were obtained before, during and post placement completion. Reflections from academic staff involved in the project were gathered following placement completion. The analysis of these sources of data revealed that, while challenging, this placement strengthened students’ collaborative problem-solving, advocacy skills and clinical competence.